Synthesis and characterization of new iminopyridazine butyronitrile hydrobromides (Journal of Bangladesh Academy of Sciences, 2021)
In this study, general methods were applied for the preparation of new iminopyridazine butyronitriles. A series of six new 4-(3-aryl-1,6-dihydro-6-iminopyridazin-1-yl)butyronitrile hydro-bromides (2a-2f) (Scheme 1) have been prepared starting from commercially available 3-amino-6-chloropyridazine in two steps with good yields. The synthesized compound’s structures were characterized by IR, 1H NMR and high-resolution mass structures spectral (HRMS) data.Journal of Bangladesh Academy of Sciences, Vol. 44, No. 2, 131-138, 2020